Can Escherichia coli fly? The role of flies as transmitters of E. coli to food in an urban slum in Bangladesh. Issue 1 (7th December 2017) - Lindeberg, Yrja Lisa; Egedal, Karen; Hossain, Zenat Zebin; Phelps, Matthew; Tulsiani, Suhella; Farhana, Israt; Begum, Anowara; Jensen, Peter Kjær Mackie
Abstract: Objective: To investigate the transmission of faecal bacteria by flies to food under natural settings. Methods: Over a period of 2 months, paired (exposed and non‐exposed) containers with cooked rice were placed on the ground in kitchen areas in an urban slum area in Dhaka, Bangladesh, and the numbers of flies landing on the exposed rice were counted. Following exposure, the surface of the rice was microbiologically and molecularly analysed for the presence of Escherichia coli and genes of diarrhoeagenic E. coli and Shigella strains. Results: Rice was at greater risk ( P < 0·001) of being contaminated with E. coli if flies landed on the rice than if no flies landed on the rice (odds ratio 5·4 ( P < 0·001, 95% CI: 2·5–11·7). Mean contamination in exposed rice samples ( n = 60) was 3·1 × 103 CFU/g (95% CI: 2·2 × 103–4·0 × 103). Furthermore, for approximately half of the observed fly landings, the average CFU per fly landing was >0·6 × 103 CFU. Genes of diarrhoeagenic E. coli and Shigella species were detected in 39 of 60 (65%) of exposed rice samples. Two fly species were identified: the common housefly ( Musca domestica ) and the oriental latrine fly ( Chrysomya megacephala ). Conclusion: Flies may transmit large quantities of E. coli to food under field settings. The findings highlight the importance of implementing control measures to minimise exposure of food to flies to ensure food safety. Fly control measures should be considered for the prevention of diarrhoeal diseases caused by E. coli .